Steric control of redox events in organo-uranium chemistry: Synthesis and characterisation of U(v) oxo and nitrido complexes - Tsoureas, Nikolaos; Kilpatrick, Alexander F.R.; Inman, Christopher J.; Cloke, F. Geoffrey N. (Chemical Science, 2016)
The synthesis and molecular structures of a U(v) neutral terminal oxo complex and a U(v) sodium uranium nitride contact ion pair are described. The synthesis of the former is achieved by the use of tBuNCO as a mild oxygen transfer reagent, whilst that of the latter is via the reduction of NaN3. Both mono-uranium complexes are stabilised by the presence of bulky silyl substituents on the ligand framework that facilitate a 2e- oxidation of a single U(iii) centre. In contrast, when steric hindrance around the metal centre is reduced by the use of less bulky silyl groups, the products are di-uranium, U(iv) bridging oxo and (anionic) nitride complexes, resulting from 1e- oxidations of two U(iii) centres. SQUID magnetometry supports the formal oxidation states of the reported complexes. Electrochemical studies show that the U(v) terminal oxo complex can be reduced and the [U(iv)O]- anion was accessed via reduction with K/Hg, and structurally characterised. Both the nitride complexes display complex electrochemical behaviour but each exhibits a quasi-reversible oxidation at ca. -1.6 V vs. Fc+/0.